Hippocampal and striatal M1‐muscarinic acetylcholine receptors are down‐regulated following bilateral vestibular loss in rats. Issue 12 (13th September 2016) - Aitken, Phillip; Benoit, Alice; Zheng, Yiwen; Philoxene, Bruno; Le Gall, Anne; Denise, Pierre; Besnard, Stephane; Smith, Paul F.
Abstract: Permanent vestibular loss has detrimental effects on the hippocampus, resulting in a disruption to spatial learning and memory, hippocampal theta rhythm and place cell field spatial coherence. Little is known about the vestibular system‐related hippocampal cholinergic transmission. Since the pharmacological blockade of muscarinic acetylcholine (ACh) receptors within the hippocampus produces deficits in learning and memory, we hypothesized that ACh receptors may at least partly support the integration of vestibular input. Consequently, we examined the expression of M1 muscarinic ACh receptors in the hippocampus at 7 and 30 days following bilateral vestibular lesions (BVL) in rats using autoradiography. Animals were divided into sham ( n  = 12) and BVL ( n  = 11) groups. BVL animals received intratympanic injections of sodium arsanilate (30 mg/0.1 ml) under isoflurane anesthesia and sham animals received the same volume of saline. Analysis of the brain tissue revealed a significant reduction in the number of M1 receptors throughout the hippocampus and striatum at 30 days ( P  ≤ 0.0001), but not at 7 days following BVL. This suggests that the changes in learning and memory seen following vestibular damage may be in part due to the loss of M1 muscarinic receptors in the hippocampus and striatum. © 2016 Wiley Periodicals, Inc.